The impact of frailty on failure-to-rescue in geriatric trauma patients: A prospective study. Issue 6 (December 2016) - Joseph, Bellal; Phelan, Herb; Hassan, Ahmed; Orouji Jokar, Tahereh; O'Keeffe, Terence; Azim, Asad; Gries, Lynn; Kulvatunyou, Narong; Latifi, Rifat; Rhee, Peter
Abstract : INTRODUCTION: Failure-to-rescue (FTR) (defined as death from a major complication) is considered as an index of hospital quality in trauma patients. However, the role of frailty in FTR events remains unclear. We hypothesized that FTR rate is higher in elderly frail trauma patients. METHODS: We performed a prospective cohort study of all elderly (age ≥ 65 years) trauma patients presenting at our level one trauma center. Patient's frailty status was calculated utilizing the Trauma Specific Frailty Index (TSFI) within 24 hours of admission. Patients were stratified into non-frail, pre-frail, and frail. FTR was defined as death from a major complication (respiratory, infectious, cardiac, and renal). Binary logistic regression analysis was performed after adjusting for age, gender, injury severity (ISS), and vital parameters to assess the relationship between frailty status and FTR. RESULTS: A total of 368 elderly trauma patients were evaluated of which 25% (n = 93) were non-frail, 38% (n = 139) pre-frail, and 37% (n = 136) frail. Overall, 30% of the patients developed in-hospital complications; of them, mortality occurred in 26% of the patients (FTR group). In the FTR group, 69% of the patients were frail compared to 17% pre-frail and 14% non-frail ( p = 0.002). On multivariate regression analysis for predictors of FTR, frail status was an independent predictor of FTR (OR [95% CI] = 2.67 [1.37–5.20]; p = 0.004). On sensitivity analysis, positive predictive value of TSFI for FTR was 69% and negative predictive value for FTR was 67%. CONCLUSION: In elderly trauma patients, the presence of frailty increased the odds of FTR almost threefold as compared to non-frail. Although FTR has been considered as an indicator of health care quality, the findings of this study suggest that frailty status independently contributes to FTR. This needs to be considered in the future development of quality metrics, particularly in the case of geriatric trauma patients. LEVEL OF EVIDENCE: Prognostic study, level II. Abstract : Supplemental digital content is available in the text.